SANTARA CROWDFUNDING MARKETING - Gustina Gustina (Cross-Border Journal of Business Management, 2022)
Santara is a service that utilizes financial technology that is engaged in crowdfunding. This paper aims to describe, namely: 1) the media used by intermediaries in marketing; 2) Intermediate marketing targets. Researchers used qualitative research procedures with documentation data collection techniques. The results showed that, 1) The media used by Santara, namely: website, Instagram, Facebook, Twitter, YouTube, and applications on the Play Store 2) Santara's marketing target is Small and Medium Enterprises. However, between grouping into two main targets, namely a) people who want to own a business, but they do not have the skills, time or capital; b) business people who need funding to expand their business development. This is in line with Santara's vision, namely Scale Up Small and Medium Enterprises, Scale Up the Indonesian Economy.